Siirtolaisoppilas Ruotsin kouluyhteisössä : sosiometrinen tutkimus - Lasonen, Kari (1981)
The current study investigates the social structures of Swedish-medium and compound classes consisting of Swedish pupils and mainly Finnish immigrant pupils. The areas concerning the study are as follows: I) The apportionment of social status within the classes. 2) Motives for selection as expressed in sociometric choices. 3) Evaluations of personality traits of the chosen and the rejected. and pupils' evaluations of their own personalities. 4) Integration of the pupils into their classes. The theoretical basis for the study was provided by Moreno’s sociometric theory. The numbers of pupils receiving instruction in these classes were as follows: Swedes 620. Finns 244. of other stock 69. For the sake of comparison, the study includes Finnish-medium classes (n = 139 pupils) and classes from schools in Finland (n = 1365). The instrument for gathering the data was a sociometric test where the choices made were connected with group work (selection of friends and leaders on the one hand. and rejections on the other). In addition to the aforementioned, the testees wrote reasons for their choices. and. by the semantic differential technique, they evaluated the personal traits of those primarily selected and rejected and themselves. Social status received a distribution in accordance with the laws propounded in Moreno’s theory, the clearest criteria being the sex of the pupil. An additional factor in the formation of social relationships was nationality. The Swedes showed a marked tendency to friendships with pupils of their own nationality. The Finns, on the other hand, relatively frequently opted for Swedish pupils of the same sex, even though they too showed a general preference for their in-group. Relations between the Swedes and the Finns seemed to be worst in classes, where there was an approximate numerical balance between the two groups. Success in schoolwork was also connected with the sociometric choices. The popular pupils did better at school than the less popular. Reasons given for choices made were based mainly on motives directed towards the object of choice. On the basis of personality traits, the Swedes tended to have. on an average, higher self-esteem than the others. A positive evaluation has been given to those given preference in the formation of working groups and to those chosen as leaders. On the other hand, those rejected have been given a negative evaluation.